2008
DOI: 10.1002/mus.20934
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of perception threshold testing and thermal‐vibratory testing

Abstract: Current perception threshold testing (CPT) is thought to selectively activate and measure three types of afferent nerves. However, it has not been standardized or compared with better-studied methods of sensory testing. Our objectives were to determine the relationship between CPT (2000 Hz, 250 Hz, 5 Hz) and quantitative sensory testing (QST) using vibratory and heat thresholds, and to assess the test-retest reliability of both methods. Twenty-seven healthy women were enrolled. Each woman underwent CPT and QST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
5
18
2
Order By: Relevance
“…However, frequency-based neuroselectivity is far from consensus. In the literature there are several studies that agree with the existence of such phenomenon (Lowenstein et al, 2008;Masson et al, 1989;Matsutomo et al, 2005;Nishimura et al, 2004;Tierra-Criollo et al, 2006), and others that disagree (Tack et al, 1994;Vinik et al, 1995).…”
Section: Introductionmentioning
confidence: 91%
“…However, frequency-based neuroselectivity is far from consensus. In the literature there are several studies that agree with the existence of such phenomenon (Lowenstein et al, 2008;Masson et al, 1989;Matsutomo et al, 2005;Nishimura et al, 2004;Tierra-Criollo et al, 2006), and others that disagree (Tack et al, 1994;Vinik et al, 1995).…”
Section: Introductionmentioning
confidence: 91%
“…This finding of hyposensitivity at T12 contrasts with the results of our prior study carried out using CPT that found no difference in sensitivity, 9 a discrepancy that is not surprising given the known inconsistency in findings when these two testing modalities are utilized on the skin: one study comparing CPT and QST demonstrated only a moderate correlation between CPT at 5 Hz and thermal stimuli and also demonstrated that thermal stimuli had superior reproducibility when tested on the hand. 32 The finding of hyposensitivity to stimuli is not novel, as similar hyposensitivity has been documented in patients with IBS, but has not been found in PBS patients before. Similar hyposensitivity to additional stimuli in the setting of chronic background pain has been documented in other studies of chronic pain [33][34][35] and is thought to reflect either activity of diffuse noxious inhibitory control (DNIC) mechanisms, 36 and/or adaptation, 31 in which additional stimuli are perceived as relatively mild because they occur against a background of chronic pain.…”
Section: Discussionmentioning
confidence: 83%
“…This finding is consistent with our prior findings that PBS patients had decreased habituation to non-noxious repeated supra-threshold CPT at the same dermatomes. 9 Habituation, a decrease in responsiveness to a stimulus when that stimulus is presented repeatedly or for a prolonged time, is an important mechanism that allows us to ignore non-noxious stimuli, 32,33 and is thought to be mediated by cellular plasticity with depression of responses during repetitive stimulation. Habituation is usually described in the context of repetitive stimuli rather than continuous stimuli we applied in this study, but similar mechanisms may apply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients detect thermal stimuli more easily than CPT stimuli. 30,31 Finally, this method is only a semiobjective test in that it requires subjective feedback from patients regarding the detection of electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%